Effects of Metformin Treatment on Homocysteine Levels and Metabolic Parameters of Women With Polycystic Ovary Syndrome - Soheila Riahinejad; Ahmad Mirdamadi; Elham Alizadeh (Tehran University of Medical Sciences, 2016)
Objective: Polycystic ovary syndrome (PCOS) is one of the most common endocrine disorders in women. Metformin is a biguanide commonly used to improve PCOS symptoms. Effect of metformin on the levels of serum homocysteine (Hcy) in PCOS women is unclear. The aim of this study is evaluating the effect of metformin administration on serum Hcy levels and metabolic parameters of PCOS patients. Materials and methods: Thirty three patients with PCOS were enrolled in this study who were selected randomly. All patients received metformin from the fifth day of menstrual cycle at a dose of 850 mg (one tablet daily) for 3 months. Body mass index, Triglycerides, total cholesterol, high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), fasting blood sugar and homocysteine levels were recorded at entry into the study and after 3 months treatment. Results: BMI, plasma Homocysteine concentrations and fasting blood sugar levels were significantly (p < 0.05) decreased after the treatment period. No significant changes were observed in the lipid profiles of patients. There was a weak negative correlation between homocysteine and LDL cholesterol serum levels (p = 0.04, r = -0.27). Conclusion: Treatment with metformin in PCOS women may lead to beneficial effects in terms of BMI, plasma homocysteine concentrations and fasting blood sugar with no remarkable effect on lipid profile.